1992
DOI: 10.1210/me.6.4.607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormone and cellular modulators of protein phosphorylation on transcriptional activity, DNA binding, and phosphorylation of human progesterone receptors

Abstract: Human progesterone receptors (PR) in T47D breast cancer cells are synthesized as two different sized proteins, PR-A [94 kilodaltons (kDa)] and PR-B (120 kDa). Progestin addition to cells (in vivo) causes a 2-fold increase in total phosphorylation of PR and an increase in the apparent mol wt of both PR-A and PR-B on sodium dodecyl sulfate (SDS)-gels. Time-course experiments showed that increased PR phosphorylation that results from hormone addition is a multistep process and involves a rapid increase into total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 0 publications
2
40
1
Order By: Relevance
“…Activation of the cAMP signalling pathway or inhibition of cellular phosphatase activity can synergistically stimulate transcription from the MMTV promoter in the presence of glucocorticoids or progestins (10,22,47,53,57). We confirm that the response of transiently introduced MMTV reporter cassettes to GR and PR is cooperatively enhanced by cAMP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Activation of the cAMP signalling pathway or inhibition of cellular phosphatase activity can synergistically stimulate transcription from the MMTV promoter in the presence of glucocorticoids or progestins (10,22,47,53,57). We confirm that the response of transiently introduced MMTV reporter cassettes to GR and PR is cooperatively enhanced by cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, nuclei were thawed on ice and washed once in 10 mM Tris (pH 8.0)-5 mM MgCl 2 -40% glycerol-2.5 mM dithiothreitol (DTT). Nuclear pellets were resuspended in 200 l of the wash buffer, to which an equal volume of reaction buffer (10 Slot blots were prepared as follows. DNA fragments containing sequences from actin, MMTV ras (pM18), MMTV CAT (pM25), or pUC18 were isolated and denatured in 10 mM HEPES (N-2-hydroxyethylpiperazine-NЈ-2-ethanesulfonic acid) (pH 8.0)-1 mM EDTA-6% formaldehyde by boiling for 1 min followed by incubation at 60ЊC for 1 h. Fragments were then diluted with 20ϫ SSC and applied to a nylon membrane (Hybond; Amersham) in 1-g aliquots by using a slot blot vacuum apparatus (Hoefer).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, additional evidence suggests that modulators of phosphorylation may not even have the same effects on PR from different species. Beck et al [6] reported that the transcriptional activity of human PR is not stimulated by 8-bromo-CAMP or okadaic acid in the absence of progesterone treatment. However, these compounds were found to enhance progesterone-dependent transactivation of gene expression by three-to fourfold over the levels induced by progesterone alone.…”
Section: Steroid Receptorsmentioning
confidence: 99%